Persistent transmission of soil-transmitted helminths despite 16 years of uninterrupted Mebendazole- and ivermectin-based preventive chemotherapy in the Lomie Health District (East Region, Cameroon): The emergency of complementary control strategies. - Arnauld Efon-Ekangouo; Virtue F De-Gaulle; Yannick Emalio; Verner N Orish; Linda Djune-Yemeli; Michèle L Simo-Simo; Martine A Tsasse; Laetitia Mbakam; Hugues C Nana-Djeunga; Joseph Kamgno (PLoS Neglected Tropical Diseases)
Background The control of the Soil-Transmitted Helminths (STH) infections primarily relies on the school-based Preventive Chemotherapy (PCT) with mebendazole. Given the efficacy of ivermectin on STH, the control of the latter is expected to be potentialized in areas where ivermectin is also distributed for onchocerciasis and/or lymphatic filariasis control/elimination. This study aimed to assess the prevalence and intensity of STH in the Lomie Health District where annual school-based deworming campaigns and community-directed treatments with Ivermectin have been underway for almost two decades. Methodology/principal findings A quantitative cross-sectional study was conducted in 10 schools of the Lomie Health District, East Region, Cameroon. Stool samples were collected from school-aged children and analysed using the Kato-Katz technique. Semi-structured questionnaires were administered to enrolees to assess compliance with water, sanitation, and hygiene (WASH). Of the 491 children (median age: 9 years; IQR: 7-10) enrolled, 83.9% (95% CI: 80.3-87.1) were infected with at least one STH species. Trichuris trichiura was the predominant species (78.5%), and no hookworm was found. The prevalence trend slightly decreased between 1987 and 2010 (~8%) and remained unchanged since 2010 (p-value = 0.05). Overall, 46.8% and 41.8% of children were heavy-to-moderately infected with Ascaris lumbricoides and T. trichiura. Poor hand hygiene (OR: 2.24, 95% IC: 1.4-3.4, p-value = 0.0002) and the use of river as a source of drinking water (OR: 14.8, 95% IC: 6.9-33.3, p-value = 0.0001) were the main risk factors associated with the STH infection in Lomie Health District. Conclusions/significance The persistent high prevalence and intensity of STH infection despite 16 years of mebendazole-based PCT and expected collateral impact of ivermectin mass distribution, points to plausible implementation gaps, poor compliance to WASH or sub-optimal efficacy of the anthelminthics used. This study highlights the need to further assess the cause of the persistent high prevalence and implement context-adapted control measures in order to curb STH transmission.